Roles of Gremlin1 and Gremlin2 in Regulating Ovarian Primordial to Primary Follicle Transition - Nilsson, Eric E. (2014)
A network of extracellular signaling factors has previously been shown to act in concert to control the ovarian primordial to primary follicle transition. The current study was designed to investigate the roles of the endogenous bone morphogenetic protein (BMP) inhibitors Gremlin1 (GREM1) and Gremlin2 (GREM2) in primordial follicle transition in the rat ovary. GREM1 and GREM2 treatment were found to reverse the effects of Anti-Müllerian Hormone (AMH) to inhibit follicle transition in a whole ovary culture system. GREM1 reversed the effect of bone morphogenetic protein 4 (BMP4) to stimulate primordial follicle transition. Immunohistochemical studies showed that GREM2, but not GREM1, was present in primordial follicles suggesting GREM2 may regulate primordial follicle transition in vivo. Co-immunoprecipitation studies indicated that GREM2 directly binds to AMH, as well as to BMP4. Transcriptome analyses of ovaries treated with GREM2 or GREM1 yielded negligible numbers of differentially expressed genes, suggesting the immediate effects of GREM2 or GREM1 appear to be at the level of protein-protein interactions, rather than direct actions on the cells. A number of other ovarian growth factors were found to influence the expression of Grem2. Observations suggest that Grem2 is a part of the signaling network of growth factors that regulate the primordial to primary follicle transition. Insights into the regulatory networks affecting the pool of primordial follicles is important to understand the molecular basis for reproductive diseases such as primary ovarian insufficiency (POI).